Anatomical and Morphological Characteristics of Burmese Python (Python Molurus Bivittatus) Raised in Captivity and Pathological Changes in It - Lyubchenko, E. N.; Dyachenko, M. Yu; Popova, D. A. (Russian Journal of Veterinary Pathology, 2025)
Introduction . The Burmese python (Python Molurus Bivittatus) is the third largest snake species in the world. In the wildlife, this snake breed is most often found in the countries of South and Southeast Asia, however, in recent years, these beautiful and docile reptiles have become popular around the world as pets. Burmese pythons are kept and bred by specialists in zoos and at zoo exhibitions as well as by amateurs. For keeping at home, it is recommended to purchase a specimen born and raised in captivity and create for it conditions that imitate its natural habitat. Pythons originate from the tropical and subtropical zones, therefore, when kept at home, high air humidity should be maintained, and a water reservoir should be provided for the semi-aquatic reptiles to bathe, which is especially important for correct snake molting. Unfortunately, more and more often these exotic animals become patients of veterinary clinics or die due to various reasons. The aim of the study is to establish the anatomical and morphological characteristics of Burmese python specimens raised in captivity, as well as pathological changes in them upon death. Materials and Methods . In 2024–2025, two corpses of Burmese python (male and female) from a private collection were delivered to “Khimera” veterinary clinic (Ussuriysk, Primorsky Territory). Cytological, bacteriological and histological studies were carried out to establish the cause of death. The studies were carried out in an artificially lighted dissection room using the method of complete autopsy during which the metric parameters of organs, as well as pathological changes in them were established. Results . It was determined that the morphometric parameters of the body and internal organs in male and female Burmese pythons differed in size related to the age, whereas some organs were almost of the same length regardless of sex and age. It was established that death of the male python occurred due to acute pneumonia, which could become a background reason for probable drowning. The female python died from acute pneumonia caused by the bacterium Ochrobactrum anthropi. Discussion and Conclusion . The data obtained during the study of the anatomical and morphological characteristics of the internal organs of male and female specimens of Burmese python, and pathological changes in the organs of reptiles upon death, can be used in the practical work of veterinarians and herpetologists.